Managing MOOC Project Development - Terry, Lucas; Hafizah, Abdul Halim Yun (Centre for Applied Learning UNIMAS, 2021)
Objective: To introduce features in Microsoft Teams for MOOC project development, management, resources, and progress monitoring.